1970
DOI: 10.3329/bjar.v33i4.2286
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of sulphur levels on yield, storability and economic return of onion

Abstract: The experiments were carried out at the Regional Agricultural Research Station, Rahmatpur, Barisal during the rabi seasons of 2001-2002 and 2002-2003 to study the impact of different sulphur levels on bulb yield, storability and economic return of onion. Sulphur application had significant effect on yield components and bulb yield of onion. The highest bulb yields (19.75 and 19.88 t/ha) were obtained from sulphur levels between 60 and 75 kg/ha in two consecutive years. Both the cumulative weight and rotten lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
4
10
0
Order By: Relevance
“…Due to sulphur applications reduction of microbial infection occurs in addition to imparting firmness to potato tubers. Similar results have been also observed by Nandi et al [26] in onion, Ullah et al [27] in onion, Tripathy et al [28] in onion, Mudasir et al [6] in garlic. The results are depicted in Table 4.…”
Section: Interaction Effect Of Sulphur and Potassium On Quality Parameterssupporting
confidence: 89%
“…Due to sulphur applications reduction of microbial infection occurs in addition to imparting firmness to potato tubers. Similar results have been also observed by Nandi et al [26] in onion, Ullah et al [27] in onion, Tripathy et al [28] in onion, Mudasir et al [6] in garlic. The results are depicted in Table 4.…”
Section: Interaction Effect Of Sulphur and Potassium On Quality Parameterssupporting
confidence: 89%
“…showed that compost and vermicompost produced onion with higher bulb quality at harvesting and during storage. On the basis of the above results, and considering that earlier studies of Ullah et al . and de Souza et al .…”
Section: Introductionsupporting
confidence: 75%
“…Abou-El-Hassan et al 20 showed that compost and vermicompost produced onion with higher bulb quality at harvesting and during storage. On the basis of the above results, and considering that earlier studies of Ullah et al 21 and de Souza et al 22 indicated that sulfur fertilization during cultivation of onion is important for the formation of bioactive compounds, our starting hypothesis was that the use of sulfur-organic-based fertilizers could be able to increase in red onion the production of bioactive organosulfur compounds and antioxidants. Our specific interests were: (i) to produce very low-emission sulfur-organic-based fertilizers by using sulfur residues and organic wastes to reduce the use of chemicals, making the food production chain safe; and (ii) to increase in a sustainable way the quality of red onion, enhancing the synthesis of health-promoting organosulfur compounds.…”
Section: Introductionmentioning
confidence: 75%
“…Generally, the cumulative weight loss in the current study was found to be high in reference to the storage length that could be due to the warm storage environment that favored high rate of respiration and transpiration. The bulbs stored in bamboo platform were found in acceptable condition after 6 months of storage showing 31.40% of weight loss according to Ullah et al (2008).…”
Section: Cumulative Weight Lossmentioning
confidence: 99%